P-029 Turbulent Flow in the Venous Outflow Tract of Pulsatile Tinnitus Patients with Sigmoid Sinus Diverticulum. (29th July 2016) - Kefayati, S; Kao, E; Liu, J; Haraldsson, H; Faraji, F; Ballweber, M; Meisel, K; Halbach, V; Saloner, D; Amans, M
Abstract : Introduction/purpose: Pulsatile tinnitus (PT) has been linked to multiple anatomical variants of the venous outflow tract including sigmoid sinus diverticulum (SSD). We hypothesize that turbulence generated by the SSD, which is normally preceded by a transverse sinus stenosis (TSS), can explain the source of sound. Turbulent flow has a known association to vasculogenic bruit. Advanced magnetic resonance velocimetry (MRV) was performed in cerebral venous sinuses and internal jugular veins (IJV) to obtain both volumetric velocity and turbulence maps. Materials and methods: A series of MRI protocols was performed at 3 T for patients with suspected venous PT including contrast-enhanced MRA (CE-MRA) to delineate the anatomy and identify SSD, 4 D-flow MR to acquire time-resolved phase (velocity) and flow-encoded magnitudes in all three directions, as well as 2 D flow to obtain flow waveforms. Flow turbulence was quantified based on turbulence kinetic energy (TKE). Five SSD patients were evaluated, four of which had an associated TSS upstream from the SSD. Results: The TSS resulted in a jet of flow, the direction of which seemed to determine the position of the SSD downstream. The streamline visualization of the flow patterns revealed recirculation in the diverticulum. A helical flow pattern was also found adjacent to the jet flow opposite and downstream of the SSD (Figure 1 ). TKE mapping revealed a highly localized region of elevated TKE downstream from the stenosis extending to the opening of the diverticulum with a maximum value of 80 J/m 3 (Figure 2 ). Discussion and Conclusion: The unique flow patterns and the presence of turbulence introduced by the TSS and SSD may help explain PT in these patients. Treatment of TSS with PTA and stent implantation, or treatment of the SSD with coil embolization can potentially alter the TKE level and pattern. Disclosures: S. Kefayati: None. E. Kao: None. J. Liu: None. H. Haraldsson: None. F. Faraji: None. M. Ballweber: None. K. Meisel: None. V. Halbach: None. D. Saloner: None. M. Amans: None.